Good workers for good jobs: Improving education and workforce systems in the US - Harry J. Holzer (IZA Journal of Labor Policy, 2012)
Stagnant earnings and growing inequality in the US labor market reflect both a slowdown in the growth of worker skills and the growing matching of good-paying jobs to skilled workers. Improving the ties between colleges, workforce institutions, and employers would help more workers gain the needed skills. Evaluation evidence shows that training programs linked to employers and good-paying jobs are often cost-effective. Helping more states develop such programs and systems would help raise worker earnings and reduce inequality.
Keywords: J24; J31; 330; education; workforce; good jobs; Hochqualifizierte Arbeitskräfte; Fachkräfte; Arbeitsmarktpolitik; USA